PERANCANGAN KAPAL WISATA DENGAN LAMBUNG KATAMARAN UNTUK MENUNJANG KEGIATAN WISATA BAHARI KABUPATEN PACITAN JAWA TIMUR - Ginanjar Baskoro Aji; Eko Sasmito Hadi; Untung Budiarto (Jurnal Teknik Perkapalan, 2013)
Pacitan Regency is a region where has a prospective potential in marine tourism activites which it has a bay with its beautiful panorama. The Pacitan Regency has 7 (seven) beaches which the highest volume of visitor is located in Teleng Ria beach. The research on designing of this tour boat is expected to help the infrastructure development of marine tourism activities in Pacitan Regency. The aimed of this research is to find main dimension of the boat, lines plan, general arrangement, boat resistance, boat stability, hydrostatic characteristic and sea keeping. This research is used comparation method. The benefit of this research is to give an alternative in marine tourism in Pacitan Regency. The result of this research consists of  main dimension of ship with LPP = 10.25 m; Bm = 5.00 m; B1 = 1.20 m; T = 0.75 m; H = 1.20 m; LWL = 10.25 m, passenger = 16 persons with 2 (two) crews, ship speed = 6.89 knots with resistance = 2.14 kN.